Implementation of Hall Effect Sensors in Servo Motors to Reduce Drift - Haidar, Ahmad; Djuriatno, Waru; Nusantoro, Goegoes Dwi (Jurnal Mahasiswa TEUB, 2025)
Servo motors play a critical role in precision control systems, traditionally  relying on potentiometers for position sensing. However, potentiometers  suffer from drift due to mechanical wear and physical contact, leading to  measurement instability over time. This study investigates the implementation of Hall effect sensors as an alternative to potentiometers  to mitigate drift in servo motor position measurement. The research  methodology encompasses the design and implementation of a position  measurement system utilizing Hall effect sensors, followed by a comparative performance evaluation against potentiometers. The  experimental procedure consists of three key stages: sensor  characterization, drift analysis under both unloaded and loaded conditions, and system response assessment to a reference angle. Performance  metrics such as rise time, settling time, and steady-state error are analyzed. The results demonstrate that Hall effect sensors effectively minimize drift,  offering improved stability, reduced position deviations, and faster  response times in achieving target angles. These findings highlight the  potential of Hall effect sensors in enhancing the accuracy and reliability of  servo motor position measurement, particularly in high-precision  applications. Keywords: servo motor, drift, potentiometer, Hall effect sensor, position accuracy